2007
DOI: 10.1097/mbc.0b013e3280108e01
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia and the compound heterozygous state for methylene tetrahydrofolate reductase are independent risk factors for deep vein thrombosis among South Indians

Abstract: To investigate the role of methylene tetrahydrofolate reductase (MTHFR) (677 C-->T and 1298 A-->C), factor V (1691 G-->A), factor II (20210 G-->A) genetic polymorphisms and hyperhomocysteinemia in the aetiology of deep vein thrombosis (DVT) in 163 cases and 163 controls. Polymerase chain reaction-restriction fragment length polymorphism was used for genotyping, reverse-phase high-performance liquid chromatography for plasma homocysteine, and Student's t-test and Fisher exact tests were used for statistical ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 44 publications
2
6
0
Order By: Relevance
“…[25][26][27] That homocysteine levels are higher in a stroke population is a definite fact confirmed by the results from this study, which seems to be in agreement with most studies from across the world 28-30 as well as from India. 31 We also find in our study that the OR rises as we move from the first quartile to the fourth quartile of the homocysteine levels (Fig 2).…”
Section: Discussionsupporting
confidence: 94%
“…[25][26][27] That homocysteine levels are higher in a stroke population is a definite fact confirmed by the results from this study, which seems to be in agreement with most studies from across the world 28-30 as well as from India. 31 We also find in our study that the OR rises as we move from the first quartile to the fourth quartile of the homocysteine levels (Fig 2).…”
Section: Discussionsupporting
confidence: 94%
“…Heterozygous MTHFR C677T genotype among Saudi female patients with DVT was 6 (10%) and did not reach the significance level (P = 0.558), in agreement with a previous report stating that there is no association between MTHFR C677T and DVT [18]. Several studies revealed that the association between MTHFR C677T and the increased risk of VTE is still controversial [19]. Others suggest that the risk of this mutation is weak, increasing in older patients and with co-inheritance …”
Section: Resultssupporting
confidence: 68%
“…These mutations may or may not lead to hyperhomocysteinemia, depending on the homozygosity or heterozygosity of the mutation, coinheritance with another mutation, or the presence of concurrent B vitamin deficiency [39]. The association between MTHFR C 677 T and MTHFR A 1298 C genetic polymorphism and the increased risk for VTE is still controversial [40, 41]. Ray et al suggest that the risk of these mutations is weak and is increasing in older patients and with coinheritance with other mutations [42].…”
Section: Discussionmentioning
confidence: 99%